Case Report: Dual immunomodulatory and hematologic benefits of rituximab in refractory anemia of ANCA-associated vasculitis - Shao, Ningjun; Chai, Lingxiong; Bai, Xu; Luo, Qun (Frontiers in Immunology, 2025)
BackgroundAntineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a systemic autoimmune disease characterized by necrotizing small-vessel inflammation, frequently complicated by severe anemia and progressive renal injury. Anemia, affecting 73–92% of AAV patients, arises from multifactorial mechanisms including renal dysfunction, chronic inflammation, and iron dysregulation. Despite conventional immunosuppressive therapies, refractory anemia remains a significant challenge, with limited strategies targeting inflammation-driven hepcidin dysregulation.Case presentationA 56-year-old woman presented with myeloperoxidase-specific antineutrophil cytoplasmic antibody (MPO-ANCA) positive AAV, transfusion-dependent anemia (hemoglobin: 56 g/L), and advanced chronic kidney disease with 55% tubulointerstitial atrophy. Initial management included cyclophosphamide, glucocorticoids, erythropoietin, and transfusions, yielding only a transient rise in hemoglobin (Hb) that rapidly declined despite treatment. Following the initiation of rituximab (RTX), her Hb level improved to 88 g/L within four weeks and normalized to 127 g/L after four biweekly infusions (500 mg each). Concurrently, MPO-ANCA titers decreased from 1:1280 to 1:80, and pulmonary infiltrates resolved. However, renal function remained impaired (serum creatinine: 229 µmol/L) due to irreversible fibrosis.ConclusionsThis case demonstrates RTX’s dual efficacy in suppressing autoimmunity and alleviating anemia, potentially through indirect effects on inflammatory pathways and iron metabolism. Early RTX use may reduce transfusion dependency and help stabilize renal function in refractory AAV, though advanced fibrosis limits recovery. These findings support RTX as a first-line option in AAV patients with severe anemia and evolving renal injury.